2019
DOI: 10.1037/hea0000688
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trauma, economic hardship, and stress on neurocognition and everyday function in HIV.

Abstract: Objective: The causes of neurocognitive and everyday functioning impairment among aging people living with HIV (PLWH) are multifactorial. Exposure to stress and trauma can result in neurocognitive deficits via activation of neurological and other biological mechanisms. Methods: PLWH (n=122) and persons without HIV (n=95), 35–65 years of age, completed four questionnaires that were used to generate a trauma, economic hardship (food insecurity and low socioeconomic status), and stress composite variable (TES).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 52 publications
(60 reference statements)
0
34
0
Order By: Relevance
“…There is evidence supporting an interaction between stress and HIV on brain function. For example, in people with HIV, greater impairments in cognitive function have been associated with increased stress, and increased stress was associated with greater declines in activities of daily living in HIV+ individuals but not in those without HIV [36]. Interestingly, we did observe a differential effect of chronic and binge methamphetamine regimens on reward thresholds in TAT+ mice during doxycycline administration.…”
Section: Discussionmentioning
confidence: 57%
“…There is evidence supporting an interaction between stress and HIV on brain function. For example, in people with HIV, greater impairments in cognitive function have been associated with increased stress, and increased stress was associated with greater declines in activities of daily living in HIV+ individuals but not in those without HIV [36]. Interestingly, we did observe a differential effect of chronic and binge methamphetamine regimens on reward thresholds in TAT+ mice during doxycycline administration.…”
Section: Discussionmentioning
confidence: 57%
“…The average age for fourteen of fifteen studies, (one study reported the age range only) was 40 years. Eight were all-female studies (Malan-Muller et al, 2013 ; Rubin et al, 2017 , 2015 , 2016 ; Spies et al, 2016 , 2012 ; Spies, Fennema-Notestine, Cherner, & Seedat, 2017 ; Womersley, Spies, Seedat, & Hemmings, 2019 ) and two were all-male studies (Deiss et al, 2019 ; Pukay-Martin, Cristiani, Saveanu, & Bornstein, 2003 ), with the remainder (five studies) including both men and women (Clark, Arce Renteria, Hegde, & Morgello, 2018 ; Clark et al, 2012 ; Kapetanovic et al, 2020 ; Lin et al, 2011 ; Watson et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…There were ten case-control studies (Clark et al, 2012 ; Kapetanovic et al, 2020 ; Malan-Muller et al, 2013 ; Pukay-Martin et al, 2003 ; Rubin et al, 2017 , 2015 ; Spies et al, 2016 , 2012 , 2017 ; Watson et al, 2019 ) and five cross-sectional studies (Clark et al, 2018 ; Deiss et al, 2019 ; Lin et al, 2011 ; Rubin et al, 2016 ; Womersley et al, 2019 ). Eight studies were longitudinal in design (Malan-Muller et al, 2013 ; Rubin et al, 2017 , 2015 , 2016 ; Spies et al, 2016 , 2012 , 2017 ; Womersley et al, 2019 ) but only one of these presented longitudinal data examining the relationship between childhood trauma and HIV and change in cognition over time (Spies et al, 2017 ) and one examined the relationship between perceived stress and PTSD and NCI over time (Rubin et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations